Genome-Assisted Characterization of Lactobacillus fermentum, Weissella cibaria, and Weissella confusa Strains Isolated from Sorghum as Starters for Sourdough Fermentation - Falasconi, Irene (Microorganisms, 2020)
Sourdough fermentation of bakery products is a well-established and widespread technique to confer an added value to the resulting food. In recent decades, gluten-free raw materials have gained more attention due to the diffusion of food disorders such as coeliac disease, but, at the same time, they present difficult manipulation and scarce technological properties because of the absence of gluten. For this reason, the present work was aimed at selecting starter cultures for sourdough application that are isolated from fermentation of sorghum flour. Three isolates of Lactobacillus fermentum, Weissella cibaria, and Weissella confusa were selected for the following properties: exopolysaccharide synthesis, acidification, CO(2) production, and amylase activity. The investigated phenotypic characteristics were confirmed by genomic analyses, which also highlighted other potentially beneficial features for use in bakery products employment. These strains, together with bakery yeast, were used for bread preparation using sorghum and wheat flour and after 24 h of fermentation the resulting dough was analyzed to assess the improvement of its characteristics. The presence of lactic acid bacteria (LAB) had a great impact on the final dough, and the best preparation, from a rheological point of view, resulted in one made of sorghum and wheat flour with added LAB and bakery yeast, whose resulting characteristics were similar to all wheat flour doughs. The results of this study suggest a potential application of the selected starters in sorghum composite bread and should be validated with data from large-scale pilot tests conducted in industrial bakeries.